Factor Affecting Gross Domestic Product (GDP) Growth in United States (USA) - Saleh, Husny Gibreel Musa; Hamza, Ali; Touray, Katim (Universitas Bojonegoro, 2024)
This study looks at factors influencing the growth of the gross domestic product (GDP) in the United States from 1973 to 2022. Using a multiple regression model, the effects of FDI, rural population growth, and imports of Goods and services were examined about GDP growth. The study found that imports of goods and services, with their value having a positive impact on the dependent variable, are a significant factor in determining the economic growth of the United States. The positive relation of the Imports of goods and services and GDP, growth was attributed to be a measure to control the rising of FDI. It was also discovered that the FDI, Population growth, and rural population are not significant variables in determining economic growth. The study therefore recommends that the United States government and economists prioritize policies and strategies that promote sustainable economic growth, job creation, and innovation. This may involve measures such as investing in education and research, promoting entrepreneurship and small businesses, improving infrastructure, and maintaining a stable and predictable regulatory environment. Additionally, the United States can encourage foreign direct investment (FDI) as a way to attract capital and expertise to the country, but this would depend on the specific circumstances and potential risks and benefits of each investment.